Changes in Postpartum Insulin Requirements for Patients with Well-Controlled Type 1 Diabetes - Roeder, Hilary A.; Moore, Thomas R.; Ramos, Gladys A. (American Journal of Perinatology, 2016)
Objective To compare postpartum with preconception insulin doses in well-controlled (HbA1c ≤ 7.4%) type 1 diabetes mellitus (T1DM) and to characterize differences in postpartum insulin dosing based on infant feeding.Study Design The primary outcome in this retrospective cohort was the change in total daily insulin (TDI) from preconception to postpartum. Insulin administration (continuous subcutaneous insulin infusion [CSII] vs. multiple daily injections [MDI]), HbA1c, body mass index (BMI), and infant feeding were abstracted.Results We identified 44 women with T1DM and HbA1c ≤ 7.4%. Preconception mean BMI was 24.6 ± 3.6 kg/m2 and median (interquartile range [IQR]) HbA1c was 6.4 (6.0–6.9)%. Of these, 73% used CSII and 27% used MDI. Additionally, 80% of patients reported exclusive breastfeeding, 7% were exclusively formula feeding, and 13% used both breast milk and formula. Median (IQR) preconception TDI was 0.64 (0.49–0.69) U/kg/day, and postpartum: 0.39 (0.30–0.50) U/kg/day. Postpartum TDI was 34% lower than preconception TDI (p = 0.02). There was no difference in the postpartum TDI in patients who were breast versus formula feeding or when comparing CSII with MDI.Conclusion There was a significant decrease in the TDI required postpartum when compared with preconception. Dosages do not seem to be impacted by administration route or breastfeeding. These findings warrant consideration when dosing postpartum insulin in patients with T1DM.
Keywords: insulin dosing; postpartum insulin requirements; type 1 diabetes; preconception insulin doses